Potential Biomarkers of Insulin Resistance and Atherosclerosis in Type 2 Diabetes Mellitus Patients with Coronary Artery Disease - Sharifah Intan Qhadijah Syed Ikmal; Hasniza Zaman Huri; Shireene Ratna Vethakkan; Wan Azman Wan Ahmad (International Journal of Endocrinology)
Type 2 diabetes mellitus patients with coronary artery disease have become a major public health concern. The occurrence of insulin resistance accompanied with endothelial dysfunction worsens the state of atherosclerosis in type 2 diabetes mellitus patients. The combination of insulin resistance and endothelial dysfunction leads to coronary artery disease and ischemic heart disease complications. A recognized biological marker, high-sensitivity C-reactive protein, has been used widely to assess the progression of atherosclerosis and inflammation. Along with coronary arterial damage and inflammatory processes, high-sensitivity C-reactive protein is considered as an essential atherosclerosis marker in patients with cardiovascular disease, but not as an insulin resistance marker in type 2 diabetes mellitus patients. A new biological marker that can act as a reliable indicator of both the exact state of insulin resistance and atherosclerosis is required to facilitate optimal health management of diabetic patients. Malfunctioning of insulin mechanism and endothelial dysfunction leads to innate immune activation and released several biological markers into circulation. This review examines potential biological markers, YKL-40, alpha-hydroxybutyrate, soluble CD36, leptin, resistin, interleukin-18, retinol binding protein-4, and chemerin, as they may play significant roles in insulin resistance and atherosclerosis in type 2 diabetes mellitus patients with coronary artery disease.